INTEGRASI BUDAYA KAMPUNG NAGA SEBAGAI MITIGASI BENCANA DI KABUPATEN TASIKMALAYA PROVINSI JAWA BARAT - Setio Galih Marlyono; Tineu Indrianeu; Elgar Balasa Singkawijaya (JAMBURA GEO EDUCATION JOURNAL, 2022)
Disasters are a threat to all people living in Indonesia, as a logical consequence of Indonesia's geological conditions. Almost all regions of Indonesia have the potential for disasters. Especially for the West Java Province, especially the Regency on the south coast which has various kinds of disaster threats, such as Earthquakes, Tsunamis, Landslides, and even Fires. Likewise in Tasikmalaya Regency, in this case the Naga traditional village community. The touch of local wisdom in disaster mitigation is very interesting to learn in Kampung Naga. The research method uses a descriptive method with a field survey technique (Field Study). The results showed that, for earthquake disasters, it was minimized by the use of the dominant house material from bamboo and consuming the system of houses on stilts to dampen vibrations. In the case of landslides, on sloping land, this is handled by using stone terraces. As for the fire disaster, using a method of using a different room woven system for each room to minimize the appearance of fire so that it can be detected from outside the house.